Tumor- and osteoclast-derived NRP2 in prostate cancer bone metastases - Navatha Shree Polavaram; Samikshan Dutta; Ridwan Islam; Arup K. Bag; Sohini Roy; David Poitz; Jeffrey Karnes; Lorenz C. Hofbauer; Manish Kohli; Brian A. Costello; Raffael Jimenez; Surinder K. Batra; et al. (Bone Research, 2021)
Abstract Understanding the role of neuropilin 2 (NRP2) in prostate cancer cells as well as in the bone microenvironment is pivotal in the development of an effective targeted therapy for the treatment of prostate cancer bone metastasis. We observed a significant upregulation of NRP2 in prostate cancer cells metastasized to bone. Here, we report that targeting NRP2 in cancer cells can enhance taxane-based chemotherapy with a better therapeutic outcome in bone metastasis, implicating NRP2 as a promising therapeutic target. Since, osteoclasts present in the tumor microenvironment express NRP2, we have investigated the potential effect of targeting NRP2 in osteoclasts. Our results revealed NRP2 negatively regulates osteoclast differentiation and function in the presence of prostate cancer cells that promotes mixed bone lesions. Our study further delineated the molecular mechanisms by which NRP2 regulates osteoclast function. Interestingly, depletion of NRP2 in osteoclasts in vivo showed a decrease in the overall prostate tumor burden in the bone. These results therefore indicate that targeting NRP2 in prostate cancer cells as well as in the osteoclastic compartment can be beneficial in the treatment of prostate cancer bone metastasis.